Adverse Psychological Outcomes of Academic Delays Amidst the Covid-19 Pandemic: A Comprehensive Exploration - Hidajad, Arif (Research Horizon, 2023)
The COVID-19 pandemic has disrupted education globally, leading to academic delays for students at all levels. This paper explores the adverse psychological outcomes of these delays, focusing on higher education students. The shift to remote learning introduced challenges in self-discipline, isolation, and technology access, impacting students' emotional well-being. Uncertainty about academic timelines intensified stress, anxiety, and eroded confidence. Students navigated this uncertainty through coping mechanisms such as virtual support networks, mindfulness practices, and engaging in hobbies. Educational institutions played a critical role by providing mental health resources, fostering flexibility, and addressing the digital divide. The paper underscores the need for holistic approaches to education, adaptive curriculum design, resilience-building, educator training, and collaborative support systems. The pandemic offers an opportunity to redefine success in terms of adaptability and emotional well-being, preparing students for a changing world.